Inflammasome pathway in kidney transplantation - Granata, Simona; La Russa, Daniele; Stallone, Giovanni; Perri, Anna; Zaza, Gianluigi (Frontiers in Medicine, 2023)
Kidney transplantation is the best available renal replacement therapy for patients with end-stage kidney disease and is associated with better quality of life and patient survival compared with dialysis. However, despite the significant technical and pharmaceutical advances in this field, kidney transplant recipients are still characterized by reduced long-term graft survival. In fact, almost half of the patients lose their allograft after 15–20 years. Most of the conditions leading to graft loss are triggered by the activation of a large immune-inflammatory machinery. In this context, several inflammatory markers have been identified, and the deregulation of the inflammasome (NLRP3, NLRP1, NLRC4, AIM2), a multiprotein complex activated by either whole pathogens (including fungi, bacteria, and viruses) or host-derived molecules, seems to play a pivotal pathogenetic role. However, the biological mechanisms leading to inflammasome activation in patients developing post-transplant complications (including, ischemia-reperfusion injury, rejections, infections) are still largely unrecognized, and only a few research reports, reviewed in this manuscript, have addressed the association between abnormal activation of this pathway and the onset/development of major clinical effects. Finally, the regulation of the inflammasome machinery could represent in future a valuable therapeutic target in kidney transplantation.